Enhancing the chemoenzymatic synthesis of arabinosylated xylo-oligosaccharides by GH51 α-l-arabinofuranosidase. (12th January 2015) - Arab-Jaziri, Faten; Bissaro, Bastien; Tellier, Charles; Dion, Michel; Fauré, Régis; O'Donohue, Michael J.
Graphical abstract: Highlights: Random mutagenesis increased transglycosylation in an α-l -arabinofuranosidase. Some mutants display significant alleviation of inhibition by xylo-oligosaccharides. Reduced hydrolysis appears to be a pre-requisite for better transglycosylation. Functionally-pertinent mutations are mainly localized around subsite −1. Abstract: Random mutagenesis was performed on the α-l -arabinofuranosidase of Thermobacillus xylanilyticus in order to enhance its ability to perform transarabinofuranosylation using natural xylo-oligosaccharides as acceptors. To achieve this goal, a two-step, high-throughput digital imaging protocol involving a colorimetric substrate was used to screen a library of 30, 000 mutants. In the first step this screen selected for hydrolytically-impaired mutants, and in the second step the screen identified mutants whose global activity was improved in the presence of a xylo-oligosaccharide mixture. Thereby, 199 mutants displaying lowered hydrolytic activity and modified properties were detected. In the presence of these xylo-oligosaccharides, most of the 199 (i.e., 70%) enzymes were less inhibited and some (18) mutants displayed an unambiguous alleviation of inhibition (<25% loss of activity). More precise monitoring of reactions catalyzed by the most promising mutants revealed a significant improvement of the synthesis yields of transglycosylation products (up to 18% compared to 9% for the parental enzyme) when xylobiose was present in the reaction. Genetic analysis of improved mutants revealed that many of the amino acid substitutions that correlate with the modified phenotype are located in the vicinity of the active site, particularly in subsite −1. Consequently, we hypothesize that these mutations modify the active site topology or the molecular interaction network of thel -arabinofuranoside donor substrate, thus impairing the hydrolysis and concomitantly favoring transglycosylation onto natural acceptors.